The Effects of Atorvastatin on Cardiopulmonary Bypass Induced Inflammatory Response of Early Period and Intensive Care Unit Length of Stay After Coronary Artery Bypass Surgery - Coşkun Araz; Arash Pirat; Adnan Torgay; Muammer Yücel; Gülnaz Arslan (Galenos Yayinevi, 2011)
Objective: To evaluate the effects of preoperative using of atorvastatin on cardiopulmonary bypass induced early inflammatory response in coronary artery bypass grafting surgery. Materials and Methods: After obtaining Instutitional Ethics Committee approval and patients' written informed consent, 20 patients who were atorvastatin users and 20 matched controls were included in this prospective observational cohort study. All patients underwent CABG with CPB using standard anesthetic and surgical techniques. Blood samples were collected for measurement of serum interleukin-1 (IL-1), IL-6, tumor necrosis factor-alpha (TNF-alpha) and p-selectin levels at the beginning of the operation (T1), 5 minutes after the removing of the cross clamp (T2), 10 minutes after the end of the CPB (T3) and 6 hours of the operation (T4). Results: The groups were comparable regarding demographic features; preoperative characteristics; duration of CPB, aortic cross clamping, and anesthesia; intra- and postoperative hemodynamicparameters; inotrope and vasopressor needs; blood products and fluid requirements; and extubation times (p>0.05 for all). Compared to baseline values, in both groups serum IL-1, IL-6, TNF-alpha and p-selectin levels increased significantly at the 5 minutes after the opening of the cross clamp, termination of CPB and 6 hours after surgery (p<0.05 for all). However, there were no significant differences between the two groups at any measurement time point in terms of CPB induced inflammatory response (p>0.05 for all). Patients in atorvastatin group had a significantly shorter intensive care unit (ICU) length of stay than the control group (56.7±19.5 hours vs 72.5±26.6 hours, P=0.008). Conclusion: Pretreatment with atorvastatin did not decrease CPB induced inflammatory response in our CABG patients. The shorter length of ICU stay in our atorvastatin users needs to be further evaluated. (Journal of the Turkish Society of Intensive Care 2011; 9: 1-7)